Physical and recreational activities to promote community environmental education - Jorge Cabrera-Reyes; Elda Vázquez-Corona (Universidad de Guantánamo, 2016)
Through a diagnosis made in the distribution "Carlos Manuel de Céspedes" of Bayamon municipality, Granma province, it was determined that there were limitations regarding the needs, tastes, and recreational preferences in the adolescent population that responded to the development of an environmental culture , Which was the starting point for the programming of physical and recreational activities with this objective. For this, theoretical and empirical methods as well as statistical-mathematical methods were applied. After its application, the high level of knowledge and satisfaction of this population was corroborated, evidenced in the behavioral change experienced.